Performance Analysis of Discone Antenna for Radio Frequency Interference (RFI) Measurement - Umar, R; N. Hazmin, S; S. Marhamah, M; A. Aziz, A; A. N. Zulaikha, M; R. S. N. Dianah, A; Roshidah, M; T. Ali, M; H. Abd Rahman., N; N. Dagang, A; Jaafar, H; K. A Kamarudin, M; et al. (International Journal of Engineering and Technology, 2018)
Radio signal is basically generated from natural sources and human daily activity. In detecting radio astronomical signals from outer space, radio frequency interference (RFI) level monitoring and management are required to avoid the signalâ€™s disturbance for better radio astronomical observation. RFI profile need to be developed and the measurement should be done using appropriate antenna. Using an appropriate antenna is vital, so the signals detected are strong. This paper verified the performance of discone antenna for RFI study for Hydrogen line (HI). Three stages were performed: antenna simulation using Computer Simulation Technology (CST) Studio Suite software, antenna measurements done in anechoic chamber and RFI survey at Balai Cerap Kusza (BCK). Antenna simulation and measurement were then compared. We found that optimized frequency ranges are between 1.38 GHz and 2.14 GHz. RFI monitoring was done and we obtained the average power level of -76.2331 dBm (+/-0.7385) detected at BCK. This value exceeds the ITU-R RA.769.2 threshold level (-220 dBW) by 30.4601 dB. Â Â